Inhibition of Aryl Hydrocarbon Receptor (AhR) Expression Disrupts Cell Proliferation and Alters Energy Metabolism and Fatty Acid Synthesis in Colon Cancer Cells - Karasová, Martina; Procházková, Jiřina; Tylichová, Zuzana; Fedr, Radek; Ciganek, Miroslav; Machala, Miroslav; Dvořák, Zdeněk; Vyhlídalová, Barbora; Zůvalová, Iveta; Ehrmann, Jiří; Bouchal, Jan; Andrysík, Zdeněk; et al. (Cancers, 2022)
The aryl hydrocarbon receptor (AhR) plays a wide range of physiological roles in cellular processes such as proliferation, migration or control of immune responses. Several studies have also indicated that AhR might contribute to the regulation of energy balance or cellular metabolism. We observed that the AhR is upregulated in tumor epithelial cells derived from colon cancer patients. Using wild-type and the corresponding AhR knockout (AhR KO) variants of human colon cancer cell lines HCT116 and HT-29, we analyzed possible role(s) of the AhR in cell proliferation and metabolism, with a focus on regulation of the synthesis of fatty acids (FAs). We observed a decreased proliferation rate in the AhR KO cells, which was accompanied with altered cell cycle progression, as well as a decreased ATP production. We also found reduced mRNA levels of key enzymes of the FA biosynthetic pathway in AhR KO colon cancer cells, in particular of stearoyl-CoA desaturase 1 (SCD1). The loss of AhR was also associated with reduced expression and/or activity of components of the PI3K/Akt pathway, which controls lipid metabolism, and other lipogenic transcriptional regulators, such as sterol regulatory element binding transcription factor 1 (SREBP1). Together, our data indicate that disruption of AhR activity in colon tumor cells may, likely in a cell-specific manner, limit their proliferation, which could be linked with a suppressive effect on their endogenous FA metabolism. More attention should be paid to potential mechanistic links between overexpressed AhR and colon tumor cell metabolism.
Keywords: Akt pathway; AhR; proliferation; metabolism; fatty acid synthesis; colon cancer cells